Sonochemical Synthesis of Cu@Pt Bimetallic Nanoparticles - Henrik E. Hansen; Daniel Ø. Fakhri; Frode Seland; Svein Sunde; Odne S. Burheim; Bruno G. Pollet (Molecules, 2022)
Reducing the amount of noble metals in catalysts for electrochemical conversion devices is paramount if these devices are to be commercialized. Taking advantage of the high degree of particle property control displayed by the sonochemical method, we set out to synthesize Cu@Pt bimetallic nanocatalysts in an effort to improve the mass activity towards the hydrogen evolution reaction. At least 17 times higher mass activity was found for the carbon supported Cu@Pt bimetallic nanocatalyst (737 mA mg−1, E = <semantics>−20 </semantics><semantics>m</semantics><semantics>V</semantics>) compared to carbon supported Pt nanocatalysts prepared with the same ultrasound conditions (44 mA mg−1, E = <semantics>−20 </semantics><semantics>m</semantics><semantics>V</semantics>). The synthesis was found to proceed with the sonochemical formation of Cu and Cu2O nanoparticles with the addition of PtCl4 leading to galvanic displacement of the Cu-nanoparticles and the formation of a Pt-shell around the Cu-core.